A study in the emergence of applied behavior analysis through the referencing patterns in its founding articles. Issue 1 (2nd January 2021) - Altus, Deborah E.; Morris, Edward K.; Smith, Nathaniel G.
ABSTRACT: We examined the emergence of applied behavior analysis (ABA) through referencing patterns, analyzing 309 references cited in 36 ABA articles discerned as founding articles in prior research. We also analyzed 338 references in 26 articles in the first volume of the  Journal of Applied Behavior Analysis  ( JABA ) to see if referencing patterns changed as the field became institutionalized. We identified two research groups whose publications seemed particularly influential – the Ayllon and Wolf Groups. We also found five referencing patterns that revealed a higher frequency of: (a) journal articles, (b) applied research, (c) operant research, (d) recent publications, and (e) references to publications by Ayllon and Wolf, to co-authored publications, and to male-authored publications. The results for  JABA  were similar, suggesting these patterns were not altered by the field's institutional founding. We discuss unexpected findings (e.g., the dearth of references to Skinner and classic articles), limitations, and suggestions for future research.